PENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN MENULIS PUISI PADA SISWA KELAS VIII SMPS AL – WASHLIYAH 8 MEDAN - Pulungan, Hafni Laila; Zahara, Siti Fatimah; Lubis, Lailan Syafira Putri (Universitas Jabal Ghafur, 2024)
This research aims to reveal the effect of implementing the discovery learning model on the ability to write poetry in class VIII students at SMPS Al Washliyah 8 Medan. This research uses a quantitative experimental design using 2 groups (Two class Pretest-Posttest Design). The research mechanism includes three terms: an initial poetry writing test, the application of discovery learning, and a final poetry writing test. The population was 93 students, the sampling technique used random sampling technique. The research sample was taken randomly from classes VIII (three) and VIII (two) totaling 62 students. The application of discovery learning in learning is carried out in stages: introduction, stimulus prize for poetry text, conflict identification, data collection, data processing, creation of poetry text, presentation of the results of the work, and drawing conclusions. What will happen is that the research provides a significant disparity between the ability to write poetry of students who are taught with and without using discovery learning examples. The pre-test score for the control class was 64.64 and the experimental class was 70.71. The homogeneous post-test score for the control class was 74.70 and the experimental class was 82.58. The t-test gives a tcount value of = 11.75 which is greater than the ttable value (11.75 0.3550). This shows that the value hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Using this, it can be concluded that the use of discovery learning examples has a positive effect on the ability to write poetry in class VIII students at SMPS Al Washliyah 8 Medan for the 2023-2024 academic year.